Design, Validation, and Reliability of an Observational Instrument for Technical and Tactical Actions in Singles Badminton - Torres-Luque, Gema; Blanca-Torres, Juan Carlos; Giménez-Egido, José María; Cabello-Manrique, David; Ortega-Toro, Enrique (Frontiers in Psychology, 2020)
Technical and tactical actions are decisive in terms of badminton player competitive performance. The main objective of this research was to design, validate and estimate the reliability of an observational instrument to analyze the technical and tactical actions in individual badminton. The process was carried out in four different steps: in the first, a review of the scientific literature and a preliminary list of variables was made; secondly, a quantitative and qualitative evaluation was carried out by 10 badminton expert judges; in the third step, the content validity was calculated by means of Aikens’s V coefficient; finally, intra and inter observer reliability were tested by 2 observers specialized in badminton using the Cohen’s Kappa coefficient and the intraclass correlation coefficient. The observational instrument uses the stroke as a unit of measure, so that each time a player hits a shuttlecock, a total of 22 variables (8 contextual variables, 7 variables related to the result of the match and 7 variables related to the game) are observed. The minimum Aikens’s value was 0.58 and reliability of 0.63. In spite of these values, none of the variables had to be removed, but there were modifications in terms of drafting in